Contribution of mercury present in dental amalgams to the recognition of calcined corpses. - Santa-Duque, Carlos Andrés (2022)
n this article, a review of the subject was made by systematically searching literature in PubMed, Scopus and Google Scholar, where according to the inclusion and exclusion criteria and after the review of the summary, we obtained 48 bibliographical references and two technical sheets that were reviewed in full and included in this review. In clinical practice, some products are used that have traces up to significant amounts of mercury, a clear example is the still valid use of amalgams in dentistry, which is characterized by generating bioaccumulation processes of heavy metals in different body tissues according to some studies of toxicity. Despite the toxic consequences of contact with heavy metals through amalgams, these have been a great help in forensic sciences allowing the identification of dead bodies through diverse techniques ranging from observational methods to analytical measures that use spectrometric methods, providing a considerable tool for legal medicine, which has a positive impact in the social field, for this reason, the objective of this review is to describe the usefulness of dental amalgam analysis in the field of forensic dentistry for the recognition of burned corpses, addressing aspects such as the behavior of such amalgams at high temperatures, the relevance of mercury in forensic medicine, its detection and the report of dental identification techniques in corpses with particular characteristics such as calcination. In this review, it was found that mercury is a key element for dental identification in corpses with dental amalgams, an identification that represents the culmination of one of the main objectives of the forensic necropsy but also contributes to the speeding up of the medical-legal process, the mourning loved ones and the development of the funeral rite, which is of utmost importance in our community.